EFEKTIVITAS BELAJAR SISWA MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING PADA MATERI ALJABAR - Harwan; Antowo, Sulistyo Jeni; Novianti, Idha (Prosiding Temu Ilmiah Nasional Guru, 2023)
The purpose of this study is to find out how effective the contextual teaching and learning (CTL) approach in mathematics on the topic of algebra is discussed. This study was conducted in two cycles, with one meeting per cycle. This study uses test equipment to determine how effective student learning is. The results showed that the overall average score of student achievement indicators in cycle I was 69.23% and rose to 92.30% in cycle II. The average score of student learning outcomes in cycle I was 69.23% and rose to 85.00% in cycle II, resulting in classical completeness. According to this research, a contextual teaching and learning approach can help Grade VII junior high school students learn about algebraic material.